Asosiasi Marka Genetik dengan Pertambahan Bobot Badan Sapi Madura di Pamekasan - Suyadi Suyadi; Isnaini Isnaini; Rahayu Rahayu; Y. Nurpah (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2008)
Characteristic of DNA markers may be able to be used as useful and efficient tool to select merit animal from a population. In order to Madura cattle, growth rate is one of important traits should be considered. The aim of this study was to evaluate the association between the characteristic of DNA marker of candidate gene for growth hormone (GH) and growth rate of Madura cattle. A number of 10 female Madura cattle selected from 40 animals in average of about 18 months old were used as sample. The animal was weighed twice using electronic balance at the interval time of two months. At the simultaneous time to the animal weighing the blood sample was collected via vena jugularis 6 ml of each for DNA source. The blood sample was dropped ito polypropylene tubes containing EDTA for anti coagulant agent. DNA was isolated from leucocyte cells in the blood using salting out as standard method. PCR technique was used for amplifying the DNA using GH primer (forward: 5’-TAGGGAGGTGGAAAATGGA-3’ and reverse: 5’-GACACCTAGACAATGCG-3’). DNA polymorphism of GH gene was detected using RFLP technique by digesting the PCR-product DNA with HaeIII enzyme at position of GG*CC. The results showed that amplified DNA with this primer showed a single band of 450bp. Restriction of DNA with HaeIII enzyme resulted 4 haplotypes of uncut fragment , 2 fragments (2a and 2b), 3 fragments (3a and 3b) and 5 fragments at the position of 125bp, 200bp, 275bp and 450 bp. According to the data analysis, the non significant association was shown between specific genetic polymorphism and growth rate in this cattle. Key words: DNA marker, GH gene, growth rate, Madura cattle